Development of Immunoassays for the Iron-Regulated Proteins Ferredoxin and Flavodoxin in Polar Microalgae - Pankowski, A; Andrew McMinn (2009)
While the growth of Southern Ocean phytoplank- ton is often limited by iron availability, there are no comparable experiments on sea-ice algae. Here we assess the use of ferredoxin and ﬂavodoxin to inves- tigate the iron nutritional status of sea-ice algae and describe the development of a quantitative immuno- assay for both proteins in marine diatoms. High- afﬁnity monoclonal antibodies toward both proteins were produced from Cylindrotheca closterium (Ehrenb.) J. M. Lewin et Reimann, and these were used to develop Western blots. Western blots run on whole protein extracts detected both proteins with little cross-reactivity toward other proteins. The two proteins could be successfully quantitated when applied to gels at between 5 and 50 ng in a volume of 25 lL (0.2–2 lg Æ mL)1). Flavodoxin and ferrodox- in expression was examined in the Antarctic diatoms Entomoneis kjellmannii (Cleve) Poulin et Cardinal, Navicula directa (W. Sm.) Ralfs, Fragilariopsis curta (Van Heurck) Hust., Pseudo-nitzschia sp., Porosira gla- cialis (Grunow) E. G. Jørg., Fragilariopsis cylindrus (Grunow) Willi Krieg., Fragilariopsis sublinearis (Van Heurck) Heiden et Kolbe, C. closterium, Nitzschia leco- intei Van Heurck, and the dinoﬂagellate Polarella gla- cialis Montresor, Procaccini et Stoecker. Two Arctic isolates were also examined, Nitzschia frigida (Gru- now) and Fragilariopsis oceanica (Cleve) Hasle. Signif- icant heterogeneity of protein expression was observed despite all cultures being grown in iron- replete f ⁄ 2 medium. Only one species, F. cylindrus, displayed the expected expression of ferredoxin only in iron-replete medium. Four were observed to produce both proteins under iron-replete conditions. Ferredoxin was not detected at all in F. curta and Pseudo-nitzschia sp., but distinct ﬂavodoxin bands were observed in both of these organisms. All species examined were observed to express either ﬂavodoxin or ferredoxin or both of the proteins as determined by Western immunoblotting.